Victimological Analysis of Sexual Violence Crimes Against Children in Gorontalo Regency - Wiratma, Dewa Permana; Darmawati, Darmawati; Beddu, Sumiyati (IAIN Bone, 2024)
This research examines legal protection for children’s rights as victims of sexual violence in Gorontalo Regency and identifies factors hindering such protection. The study aims to analyze the effectiveness of legal measures in safeguarding these rights and the obstacles in their implementation. Employing an empirical research approach with qualitative methodology, data is collected through interviews and observations, offering descriptive and analytical insights into legal protection mechanisms and their challenges. Key findings reveal that child protection is regulated by Law No. 35 of 2014 on Child Protection and Law No. 11 of 2012 on the Juvenile Criminal Justice System, covering special rights, health services, and rehabilitation. However, implementation faces challenges due to resource limitations within the police and P2TP2A, lack of trained personnel, insufficient budgets, and ineffective inter-agency coordination. Additionally, social stigma and a lack of community awareness on sexual violence hinder reporting, legal proceedings, and rehabilitation. The study concludes that the primary obstacles to legal protection include limited resources, poor inter-agency coordination, and social stigma. To improve effectiveness, enhancements are needed within institutional systems, cross-sector coordination, and public education. Community support and adequate facilities are also essential for speeding up social rehabilitation and ensuring optimal fulfillment of the rights of child victims.